2014
DOI: 10.3758/s13414-014-0639-x
|View full text |Cite
|
Sign up to set email alerts
|

Visual field dependence as a navigational strategy

Abstract: Visual perception is an important component of environmental navigation. Previous research has revealed large individual differences in navigational strategies (i.e., the body's kinesthetic and embodied approach to movement) and the perception of environmental surfaces (via distance estimations), but little research has investigated the potential relationship between these sources of individual variation. An important navigational strategy is the interaction between reliance on visual cues and vestibular or pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…Presumably, when the head is level and not inclined, the brain computes distances to visual targets with respect to an assumed level ground. This represents an intermediate, neutral situation where there is neither cost nor benefit of gravity (cf [7,8,51]). In this special case, the online vestibular-gravitational signal generated by GVS does not need to be integrated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Presumably, when the head is level and not inclined, the brain computes distances to visual targets with respect to an assumed level ground. This represents an intermediate, neutral situation where there is neither cost nor benefit of gravity (cf [7,8,51]). In this special case, the online vestibular-gravitational signal generated by GVS does not need to be integrated.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly upward distances are overestimated [9]. On the other hand, the evolved navigation theory posits an evolutionary advantage in overestimating the risk of falling [10,11]. On this view, contrary to gravity theory, downward distances are overestimated.…”
Section: Introductionmentioning
confidence: 99%
“…Another factor that could have influenced distance estimation is familiarity with the location. Individual differences are to be expected in distance estimation studies if participants can use experience and familiarity with the scenery to help inform their judgments (Willey & Jackson, 2014). Although a remote channel of an open harbor was used for testing, each individual's relative familiarity with the area was not controlled for and represents a potential limitation.…”
Section: Discussionmentioning
confidence: 99%
“…Participants with significant errors are often called visual field dependent, and those with small errors or who can set a line or rod accurately to an objectively vertical position in the presence of a tilted surrounding frame, are often called field-independent. Willey and Jackson (2014) found that participants with a fear of heights relied more on visual information, compared to controls, but this difference did not reach the significance threshold. Overall, these findings contribute to evidence suggesting that a visual-vestibular component could also be present in acrophobia.…”
Section: Introductionmentioning
confidence: 85%
“…Besides (Aslan, Songu & Aslan, 2012) found was an incidence of 41% acrophobia among 34 MS patients (32 female). More recently, Willey and Jackson (2014), using the Rod and Frame Test (Witkin & Asch, 1948), tested participants with a fear of heights. This test allows the measuring of the subjective visual vertical.…”
Section: Introductionmentioning
confidence: 99%